1979
DOI: 10.1111/j.1365-2141.1979.tb03726.x
|View full text |Cite
|
Sign up to set email alerts
|

Cycles of Agglutination‐Disagglutination Induced by Ristocetin in Thrombasthenic Platelets

Abstract: An oscillatory pattern of platelet agglutination-disagglutination in response to Ristocetin (R) at narrow concentration ranges was observed in citrated platelet rich plasma (PRP) of 10 patients with Glanzmann's thrombasthenia. The cyclic pattern decreased in intensity over time, was reproducible, and was not pH dependent. Formalin-fixed thrombasthenic platelets agglutinated with R but did not show a cyclic pattern. Incubation with 2.5 microM ADP inhibited R oscillation response, but small increases in R dose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
6
0

Year Published

1980
1980
1988
1988

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 28 publications
4
6
0
Order By: Relevance
“…It is unclear whether these small aggregates are the result of platelets truly attaching to each other or rather result from the adhesion of several platelets to an underlying collagen fibril, which then simulates the appearance of an aggregate. The lOE5 antibody did not inhibit ristocetin-induced agglutination of fixed platelets and this is in accord with the findings using fixed thrombasthenic platelets (58). When ristocetin was added to PRP, 1OE5 antibody-treated platelets did not aggregate to the same final extent as normal platelets, presumably reflecting the contribution of fibrinogen binding to platelets after the release reaction was initiated; thrombasthenic platelets are known to behave in a similar way, but the complex oscillatory pattern observed with thrombasthenic platelets stimulated with ristocetin was not found with lOE5-antibody-treated platelets (58).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…It is unclear whether these small aggregates are the result of platelets truly attaching to each other or rather result from the adhesion of several platelets to an underlying collagen fibril, which then simulates the appearance of an aggregate. The lOE5 antibody did not inhibit ristocetin-induced agglutination of fixed platelets and this is in accord with the findings using fixed thrombasthenic platelets (58). When ristocetin was added to PRP, 1OE5 antibody-treated platelets did not aggregate to the same final extent as normal platelets, presumably reflecting the contribution of fibrinogen binding to platelets after the release reaction was initiated; thrombasthenic platelets are known to behave in a similar way, but the complex oscillatory pattern observed with thrombasthenic platelets stimulated with ristocetin was not found with lOE5-antibody-treated platelets (58).…”
Section: Discussionsupporting
confidence: 79%
“…The lOE5 antibody dramatically inhibited, but did not completely abolish aggregation induced by collagen when assessed by microscopic observation. Although some reports indicated that thrombasthenic platelets do not aggregate at all in response to collagen (9,30), studies by several investigators showed that small aggregates are, in fact, produced, even in patients who have no response to ADP or epinephrine (57)(58)(59)63). It is unclear whether these small aggregates are the result of platelets truly attaching to each other or rather result from the adhesion of several platelets to an underlying collagen fibril, which then simulates the appearance of an aggregate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most reports indicate that thrombasthenic platelets do not aggregate at all in response to collagen (21). However, studies by several investigators showed that small aggregates are, in fact, produced (43)(44)(45)(46). Similar results are also obtained after in vitro addition to normal platelets of a monoclonal antibody to GPIIb-IIIa complex (19).…”
supporting
confidence: 74%
“…The initial response of platelets to relatively high concentrations of ristocetin is normal in both afibrinogenemia (21) and Glanzmann thrombasthenia (30), since a different platelet receptor, namely GPIb, and a different adhesive glycoprotein, namely vWF, are involved in this response (10). At lower ristocetin concentrations, however, aggregation may be abnormal in both conditions (21,30). This finding may reflect the participation of fibrinogen in platelet aggregation mediated by vWF binding to GPIb, as suggested by recent studies (31,32).…”
Section: Discussionmentioning
confidence: 99%